2020
DOI: 10.1177/0044118x20980025
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Cyber Dating Abuse Victimization in Adolescence and Its Relationship With Health-Related Quality of Life: A Longitudinal Study

Abstract: There is currently no evidence of the relationship between cyber dating abuse (CDA) and health-related quality of life (HRQoL), especially from a longitudinal perspective. The objectives were: a) to analyze the point and period prevalence, incidence, and score changes over time of victimization by CDA; b) to compare HRQoL in the different categories of victims of CDA (nonvictims, new, ceased, intermittent, and stable victims). A three-wave longitudinal study was carried out over 13 months. The final sample was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 44 publications
6
35
1
2
Order By: Relevance
“…These results confirm the findings of other re-search works, where girls exercise more control violence [ 8 , 19 , 22 , 27 , 43 , 53 ]. The results differ with those obtained by other authors, who found that these types of behaviors were more unequally used, finding greater victimization in girls [ 36 , 51 , 54 , 55 ] and with other studies that concluded that such violence was used by both boys and girls in a similar way [ 9 , 24 , 56 , 57 , 58 ].…”
Section: Discussioncontrasting
confidence: 99%
“…These results confirm the findings of other re-search works, where girls exercise more control violence [ 8 , 19 , 22 , 27 , 43 , 53 ]. The results differ with those obtained by other authors, who found that these types of behaviors were more unequally used, finding greater victimization in girls [ 36 , 51 , 54 , 55 ] and with other studies that concluded that such violence was used by both boys and girls in a similar way [ 9 , 24 , 56 , 57 , 58 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, Ortega‐Barón et al. (2020) found that 7.6%−19.9% of boys and 15.7%−33.5% of girls reported control victimization, while 9.2%−10.8% of boys and 12.4%−23.3% of girls reported direct aggression victimization.…”
Section: Introductionmentioning
confidence: 99%
“…Considering these results, one question worth asking is whether stability in involvement as a victim may influence adolescents' behavioral and emotional adjustment. Ortega-Barón et al (2020), in a longitudinal study across three time points, recently explored the effect of cyber dating victimization on adolescent quality of life (understood as physical and psychological well-being, social support and family relationships), considering the stability of victimization. The authors identified five groups of victims: new, ceased, intermittent, stable (those who reported being victimized in the three time points), and non-victims, with this last group containing a high proportion of boys.…”
Section: Estabilidad De La Cibervictimización En La Pareja Y Ajuste P...mentioning
confidence: 99%
“…In relation to the first aim, we expected to find that cyber dating victimization would be associated with poorer psychological adjustment six months later (Cava et al, 2020;Ortega-Barón et al, 2020;Zweig et al, 2014). In relation to the second aim, we expected adolescents suffering stable or recent cyber dating victimization would report poorer levels of psychological adjustment across the six-month period (Ortega-Barón et al, 2020;Temple et al, 2016). As for the third aim, a recent meta-analysis focused on the effect of gender on cyber dating violence in adult relationships concluded that gender was not associated with cyber victimization (Gilbar et al, 2022).…”
Section: The Present Studymentioning
confidence: 99%